Developmental trends in early childhood and their predictors from an Indian birth cohort - Beena Koshy; Manikandan Srinivasan; Anuradha Bose; Sushil John; Venkata Raghava Mohan; Reeba Roshan; Karthikeyan Ramanujam; Gagandeep Kang (BMC, 2021)
Abstract Background Early childhood developmental pattern analyses not only project future cognition potential, but also identify potential risks for possible intervention. The current study evaluates developmental trends in the first 3 years of life and their predictors in a low and middle income country setting. Methods Trends of early childhood development at 6, 15, 24 and 36 months of age and their predictors were explored in a longitudinal community-based birth cohort study in an urban slum in Vellore, South India. Development was assessed using the Bayley Scales of Infant and Toddler Development-III (BSID-III). Results The birth cohort enrolled 251 children with 94, 91, 91 and 87% follow-up at 6, 15, 24 and 36 months respectively. Child development domains of cognition, language, motor and social skills showed a significant decline in scores between 6 and 36 months of age. Higher socioeconomic position (SEP) and nurturing home environment contributed to increase in cognition scores by 1.9 and 0.9 units respectively. However, stunting caused a decline in cognition scores by 1.7 units. Higher maternal cognition, higher SEP, and caregiver responsivity positively contributed to language change over time, while higher maternal depression contributed negatively. An enriching home environment, growth parameters and blood iron status had positive association with change in motor skills. Conclusions A triple intervention plan to enhance home environment and nurturance, early childhood nutrient supplementation, and maternal education and well-being might prevent child developmental decline in high risk settings.